Integrated Analysis of the ETS Family in Melanoma Reveals a Regulatory Role of ETV7 in the Immune Microenvironment - Qu, Hui; Zhao, Hui; Zhang, Xi; Liu, Yang; Li, Feng; Sun, Liyan; Song, Zewen (Frontiers in Immunology, 2020)
The ETS family modulates immune response and drug efficiency to targeted therapies, but their role in melanoma is largely unclear. In this study, the ETS family was systematically analyzed in multiple public data sets. Bioinformatics tools were used to characterize the function of ETV7 in melanoma. A prognostic model was constructed using the LASSO Cox regression method. We found that ETV7 was the only differentially expressed gene with significant prognostic relevance in melanoma. Enrichment analysis of seven independent data sets indicated ETV7 participation in various immune-related pathways. ETV7 particularly showed a strong positive correlation with CD8+ T cell infiltration. The prognostic model based on ETV7 and its hub genes showed a relatively good predictive value in training and testing data sets. Thus, ETV7 can potentially regulate the immune microenvironment in melanoma.